Veena Pointi

Ranch Hand

Posts: 442

posted 13 years ago

int a =-8;

int b=~-33;

a>>>=b;

System.out.println(a);

above code prints -8 ,how?Can anybody please explain?

Is expression like 8>>-4 valid?how to solve questions that involve shifting with negative numbers?

thanks

Veena

int b=~-33;

a>>>=b;

System.out.println(a);

above code prints -8 ,how?Can anybody please explain?

Is expression like 8>>-4 valid?how to solve questions that involve shifting with negative numbers?

thanks

Veena

SCJP1.4

"Continuous effort - not strength or intelligence - is the key to unlocking our potential."

*Winston Churchill

Sachin Tendulkar

Greenhorn

Posts: 27

posted 13 years ago

int a =-8;

int b=~-33;

a>>>=b;

System.out.println(a);

above code prints -8 ,how?Can anybody please explain?

Is expression like 8>>-4 valid?how to solve questions that involve shifting with negative numbers?

thanks

Veena

Step 1) a>>=b is expanded to

a = (int) (a >> b)

Step 2) b = ~-33

= -(-33) - 1

= 33 - 1

b = 32

(remember ~x = -(x) - 1)

Step 3) a = (int) (a >> 32)

32 in binary is represented as

00000000 00000000 00000000 00100000

When shifting numbers if the type is int then the number of places to shift is denoted by the top 5 bits of the number to shift by

in this case the top 5 bits of 32 are 00000 which is 0

so in short the expression is reduced to

Step 4) a = (int) (a >> 0)

a = (int) a

a = -8

HTH

int b=~-33;

a>>>=b;

System.out.println(a);

above code prints -8 ,how?Can anybody please explain?

Is expression like 8>>-4 valid?how to solve questions that involve shifting with negative numbers?

thanks

Veena

Step 1) a>>=b is expanded to

a = (int) (a >> b)

Step 2) b = ~-33

= -(-33) - 1

= 33 - 1

b = 32

(remember ~x = -(x) - 1)

Step 3) a = (int) (a >> 32)

32 in binary is represented as

00000000 00000000 00000000 00100000

When shifting numbers if the type is int then the number of places to shift is denoted by the top 5 bits of the number to shift by

in this case the top 5 bits of 32 are 00000 which is 0

so in short the expression is reduced to

Step 4) a = (int) (a >> 0)

a = (int) a

a = -8

HTH